Comparing the annualised dynamic shade characteristics of twenty-one tree canopies across twenty-six municipalities in a high ambient UV climate, Queensland - Australia. (July 2019) - Downs, Nathan J.; Baldwin, Louise; Parisi, Alfio V.; Butler, Harry J.; Vanos, Jennifer; Beckman, Melanie; Harrison, Simone
Abstract: Standardised assessments comparing the surveyed shade quality characteristics of twenty-one trees currently established and growing in public parks and playgrounds in Queensland, Australia are presented for informing local government, shade designers and municipal planners. Assessments focus on the ultraviolet protection of individual tree canopies which are reported in terms of the Shade Protection Index (SPI) and Ultraviolet Protection Factor (UPF) assessed at fine temporal resolution and averaged over a full calendar year. The UPF and SPI are used to determine tree species best suited for optimal shade with respect to twenty-six regional cities spanning 17 ∘ in latitude. This assessment included all local coastal districts from Bamaga ( − 10.89 ∘ S, 142.39 ∘ E) to Southport ( − 27.97 ∘ S, 153.42 ∘ E) showing a general (species dependent) decline in ultraviolet protection with increasing southerly latitude. Survey tree species are ranked and listed in order of best ultraviolet protection for respective localities enabling the quality of protection provided by living tree canopies to be compared across a range of environments. Highlights: Solar UV protection characteristics are listed for 21 trees. Trees are ranked in order of protection for 26 Queensland municipalities. The quality of tree shade decreases with increasing latitude.